Computational Approaches to Design Cytotoxic Lymphocyte (CTL) Epitope-Based Vaccine Targeting the Spike (S) Protein of SARS-CoV-2 - Mumtaz, Mehvish; Hussain, Nazim; Aslam, Ayesha; Husnain Azam, Hafiz Muhammad; Ahmad, Namra; Ramzan, Kainat (Indus Journal of Bioscience Research, 2025)
The ongoing global threat posed by SARS-CoV-2 necessitates the rapid development of effective vaccines. This study employed a computational pipeline to design a multi-epitope vaccine targeting the spike (S) glycoprotein of SARS-CoV-2. Cytotoxic T lymphocyte (CTL) epitopes were predicted using immunoinformatics tools and were screened based on their non-toxicity, immunogenicity, and antigenicity. High-affinity epitopes were sequentially linked via AAY linkers to construct a rationally designed vaccine candidate. The tertiary structure of the construct was modeled and evaluated for structural stability and desirable physicochemical properties. To assess immunogenic potential, molecular docking was performed with key immune receptors, including Toll-like receptor 3 (TLR3) and major histocompatibility complex class I (MHC-I), demonstrating strong and specific binding interactions. Furthermore, the vaccine gene was codon-optimized and in silico cloned into the pET-28b(+) expression vector, yielding a construct of 5476 base pairs. The collective in silico findings support the designed multi-epitope vaccine as a promising candidate capable of inducing robust and long-lasting cell-mediated immunity against SARS-CoV-2. Experimental validation is warranted to confirm these computational predictions.